Knowledge Management and its role in Health Care Education - Uusha Patel; Deepika S Joshi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Knowledge management in health care is a hot cake to study. Since this sector is heavily relying on theknowledge of different ingredients, and evidence based medicine is expected to be implemented in dailyhealth care activities; besides, delivery of care replies on cooperation of several partners that need toexchange their knowledge in order to provide quality of care. IN health care a knowledge based treatmentand consultancy is most required things in contemporary scenario. Since lot more challenges are lies inthe way of knowledge management. In public health decision is mainly based on data and a shift is neededtowards evidence based decision making. It is obvious that health care can profit from many advantages thatKM can provide. Nevertheless, several challenges are ahead, some are proper to KM and other particular tothe health care field. This chapter will overview KM, its methods and techniques, and provide and insightinto health care current challenges and needs, discuss applications of KM in health care and provide somefuture perspectives for KM in health care.